Robotique et principe de virtuosité - Denis Vidal (Ateliers d'Anthropologie)
Virtuosity is not an adjective that tends be to spontaneously applied to a machine. However, I would like to show that this concept allows to describe some of the developments that have taken place in robotics over the past twenty years, especially under the influence of Rodney Brooks and Luc Steels.